The effect of induced erythrocythemia upon 5-mile treadmill un time - Williams, M. H.; Wesseldine, S.; Somma, T.; Schuster, R. (Medicine & Science in Sports & Exercise, 1981)
The purpose of this experiment was to investigate the effect the infusion of 920 ml equivalent of autologous blood would have upon 5-mile time (5MT) and both local (RPE-L) and cardiovascular-respiratory (RPE-B) ratings of perceived exertion. Twelve long-distance runners undertook a series of four competitive 5MT trials on a treadmill. Four test conditions were utilized: pre-saline trial; post-saline trial after 920 ml saline solution; pre-blood trial; and post-blood trial after 920 ml equivalent of whole blood. All subjects took all trials in this double-blind placebo crossover experimental design. Running time and RPE were recorded at each 0.5 mile split. Blood samples were taken before and after each trial. The data were analyzed via a repeated-measures ANOVA. In general, the following results were noted following the blood infusion when compared with the other three trials: a significantly higher hemoglobin (Hb) concentration; a significantly lower RPE-L and RPE-B during the first two miles of the run; and a significantly faster 5MT. Within the limitations of this experiment, it was concluded that the infusion of 920 ml equivalent autologous blood would increase performance capacity in an athletic event characterized by high levels of aerobic energy expenditure.